The immune response to 6-monthly versus annual standard dose inactivated trivalent influenza vaccination in older people: study protocol for a randomised clinical trial - Young, Barnaby (2017)
Background: The seasonal influenza vaccine is less effective in older people and a single dose is unlikely to provide the year-round protection necessary for tropical climates which have year-round influenza virus activity. This study aims to assess the effect of a trivalent inactivated influenza vaccine (IIV3) booster at 180 days on haemagglutination-inhibition (HI) antibody titres for each of the influenza strains present in the administered vaccine in older people aged 65 years or above in Singapore. Methods/design: This is a single-centre, randomised, observer-blind, active-comparator controlled, parallel-group, phase IV trial in 200 adults aged 65 years or older. Study participants will be assigned to one of two groups in a 1:1 ratio and followed for 1 year, with five scheduled visits. The control group will receive IIV3 at day 1, and an active comparator (Tetanus-diphtheria-pertussis vaccine) at day 180. Participants in the experimental group will receive IIV3 containing the same strains at day 1 and day 180. Endpoints are immunological, and include measures of HI titres, microneutralisation titres (MN) and cell-mediated immunity from first vaccination up to day 360. Discussion: If superiority of 6-monthly influenza vaccination is demonstrated, this study could form the basis for a larger clinical trial with influenza infection as the primary endpoint. Trial registration: ClinicalTrials.gov, ID: NCT02655874. Registered on 12 January 2016.